(untitled) (XXI Century. Spanish Literature and Culture, 2024)
The aim of this article is to analyse Veinte años y un día, a singular work within Jorge Semprún’s literary production, published in 2003. It studies three key themes in his production: memory, fiction and identity and, at the same time, it analyses how they dialogue with each other. This is his only novel published in Spanish, set in the middle of the last century, which combines the fictional story of the Avendaño family, in which old traumas from the Civil War still resonate, and the memories of Semprún, introduced through the narrative voice and the character of Federico Sánchez, the name he used as a pseudonym when he acted as a communist clandestine during the dictatorship of Francisco Franco.